Fall Incidence and Outcomes of Falls in a Prospective Study of Adults With Rheumatoid Arthritis1. Issue 5 (23rd April 2013) - Stanmore, Emma K.; Oldham, Jackie; Skelton, Dawn A.; O'Neill, Terence; Pilling, Mark; Campbell, A. John; Todd, Chris
Abstract Objective To determine the incidence of falls and to investigate the consequences of falls in adults with rheumatoid arthritis (RA). Methods A total of 559 community‐dwelling adults with RA, ages 18–88 years (mean age 62 years, 69% women), participated in this prospective cohort study. After a detailed clinical assessment, patients were followed for 1 year, using monthly falls calendars and followup telephone calls. Followup took place in the participant's usual place of residence in the Northwest of England. Outcome measures included fall occurrence, reason for fall, type and severity of injuries, fractures, fall location, lie‐times, use of health services, and functional ability. Results A total of 535 participants followed for 1 year had a total of 598 falls. Of these participants, 36.4% (95% confidence interval 32%–41%) reported falling during the 1‐year followup period, with an incidence rate of 1, 313 per 1, 000 person‐years at risk or 1.11 falls per person. Age and sex were not associated with falls. More than one‐third of the falls were reportedly caused by hips, knees, or ankle joints "giving way." More than half of all the falls resulted in moderate injuries, including head injuries (n = 27) and fractures (n = 26). Treatment by general practitioners or other health professionals was required for 15.0% of falls, and emergency services were required for 8.8% of falls. Conclusion These results indicate that adults with RA are at high risk of falls and fall‐related injuries, fractures, and head injuries. Strategies to prevent falls in adults with RA must be prioritized to reduce falls, fall‐related injuries, and fractures.